PENGEMBANGAN VCD PEMBELAJARAN PEMBALIKAN RENANG GAYA PUNGGUNG UNTUK PELATIH DAN ATLET PEMULA KLUB RENANG KABUPATEN MALANG - SHANDY PIETER PELAMONIA (Universitas PGRI Adi Buana, 2017)
Reversal backstroke is a movements performed by a swimmer to turn around after most of his body touching the wall of the pool. Reversal will support the swimmers and the time taken to avoid disqualification of the race. Beside the swimmer must do the best reversal backstroke, do the instruction from the choach’s or guidebook to best performance,it is good if there a media to the coach and swimmer as modelling via learning video in a Video Compact Disk (VCD). The researcher aim to develop the Reversal Backstroke Learning Video Compact Disk (VCD) that canasisst coaches in conveying the material reversal backstroke and the beginner swimmer easier tolearn reversal backstroke. The researcher modified Gall Borgdan’s development model to a simple model. This result showed that this product can be used for swimming choaches and beginner swimmers in swimming club The Dictrict of Malang. The result from the professional is the advice and suggestion for this product.